Sosialisasi Bijak Menggunakan Gadget untuk Edukasi Orang Tua dalam Mendampingi Anak Belajar - Nova Tri Romadloni; Fatimah Hasna Karima; Mariyanto Mariyanto (Yayasan Literasi Sains Indonesia, 2025)
The use of gadgets has become an essential part of daily life, including in supporting children’s learning processes. Gadgets provide wide access to information, interactive educational applications, and opportunities to develop digital skills. However, excessive use without proper guidance can lead to negative impacts such as physical health problems, digital addiction, decreased concentration, and reduced social interaction. These challenges highlight the crucial role of parents as guides, supervisors, and role models in ensuring wise gadget use. This community service program aimed to educate parents, particularly PKK mothers in Dawung Village, on practical strategies for accompanying children in their use of gadgets. The activities were carried out through socialization sessions, interactive discussions, and quizzes. The discussion revealed major issues faced by parents, such as difficulty in limiting screen time, children’s preference for gaming over learning, and limited knowledge of educational applications. Meanwhile, the quiz results indicated that most participants achieved “good” (45%) and “very good” (37.5%) categories, with an average score of 72, showing improved understanding after the program. This program concludes that family digital literacy can be strengthened through interactive socialization that actively involves participants. With consistent parental guidance, gadgets can be directed to become a healthy, productive, and safe learning tool for children’s development.